An aggressive early gastric cancer: Kodama's PenA type. Issue 8 (August 2018) - Morgagni, Paolo; Solaini, Leonardo; Saragoni, Luca; Bencivenga, Maria; Fumagalli Romario, Uberto; Graziosi, Luigina; Marino, Elisabetta; Marrelli, Daniele; Rausei, Stefano; Rosa, Fausto; Scarpi, Emanuela; Tomezzoli, Anna; et al.
Abstract: Background: To investigate the role of Kodama PenA subtype in influencing survival in patients with early gastric cancer (EGC). Methods: All patients surgically treated for EGC at 7 Italian centers (Forlì, Varese, Siena, Verona, Milan, Rome and Perugia) belonging to the Italian Research Group for Gastric Cancer (GIRCG) from January 1982 and December 2009 were included. Results: PenA patients were 230 (21.5%) while other types were 839 (78.5%). Nodal metastases were more common in PenA (30.7%) than non-PenA (10.4%) EGCs. Among preoperative variables, only age (OR 1.02; 95% CI 1.00–1.03, p = 0.009) and macrotype III (OR 1.95; 95% CI 1.39–2.75, p = 0.0001) were significantly associated with Pen A type. Survival analysis performed on N0 patients demonstrated that only size >2 cm (HR 1.85; 95% CI 1.12–3.05, p = 0.017) and age (HR 1.06; 95% CI 1.03–1.08, p < 0.0001) were independent poor prognostic factor. Among N+ patients age (HR 1.04; 95% CI 1.00–1.07, p = 0.048), number of positive lymph nodes (HR 1.13; 95% CI 1.05–1.20, p = 0.0002) and PenA (HR 4.23; 95% CI 1.70–10.55, p = 0.002) were significantly correlated with poor prognosis at multivariate analysis. Conclusions: Kodama PenA subtype was the most powerful independent prognostic factor in patients with nodal metastases. Its status should always be investigated in EGCs patients.